ANALYSIS OF GERMAN NON-PROFIT ORGANIZATION ACTIVITIES NAMELY DIE BRÜCKE FOUNDATION IN JAKARTA VIEWED FROM NEOLIBERALISM PERSPECTIVE - Hidayat, Syaimma Nur (Jurnal Kelola: Jurnal Ilmu Sosial, 2023)
Poverty is a global crisis that cannot be ignored. Poverty can be reduced by measuring empowerment, participation, and social mobilization. These programs can be channeled by various non-profit organizations that are separated from government intervention, such as foundation. Die Brücke foundation is a non-profit organization of a German expatriate community and Indonesian citizens who has been carrying out social activities with Indonesian institutions to help the society who live in poverty in Jakarta and its surroundings for the past 40 years. This study applied the concept of community development of Etienne Wenger in analyzing the activities of the foundation over some time. This study also used neoliberalism theory to achieve a perspective that the influence of non-governmental institutions has a vital role in the cooperative relations between citizens. The result of this study revealed that the presence of foreign organizations will assist social institutions and the Indonesian government in the implementation of national development in Indonesia. The neoliberal perspective proved that cooperation in the social field generates usefulness.